Repeated load triaxial testing of soils - Hyde, A.F.L. (1974)
Samples of an over-consolidated saturated silty clay, Keuper marl, and a partially saturated granular material, Breedon gravel, have been used in a triaxial test programme, with a view to characterising certain aspects of the material behaviour for use in a flexible pavement design procedure.